2023
DOI: 10.3389/fpls.2022.1098560
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide association study of yield-related traits in common wheat (Triticum aestivum L.) under normal and drought treatment conditions

Abstract: The primary goal of modern wheat breeding is to develop new high-yielding and widely adaptable varieties. We analyzed four yield-related agronomic traits in 502 wheat accessions under normal conditions (NC) and drought treatment (DT) conditions over three years. The genome-wide association analysis identified 51 yield-related and nine drought-resistance-related QTL, including 13 for the thousand-grain weight (TGW), 30 for grain length (GL), three for grain width (GW), five for spike length (SL) and nine for st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 72 publications
0
7
0
Order By: Relevance
“…Interestingly, studies like the one conducted by Zhao et al [65] have observed that variations in the magnitude of the expression response of some genes to heat stress correlate directly with the structure of HSEs and, importantly, their quantity. In certain genes, such as cup1 in S. cerevisiae or hsp70 in C. elegans, which have two or three HSEs, there is a demonstrated direct relationship between the number of HSEs and the quantity of transcript produced.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, studies like the one conducted by Zhao et al [65] have observed that variations in the magnitude of the expression response of some genes to heat stress correlate directly with the structure of HSEs and, importantly, their quantity. In certain genes, such as cup1 in S. cerevisiae or hsp70 in C. elegans, which have two or three HSEs, there is a demonstrated direct relationship between the number of HSEs and the quantity of transcript produced.…”
Section: Discussionmentioning
confidence: 99%
“…In a more recent study, Zhao et al [65] performed a pioneering genome-wide analysis of T. aestivum L., discovering 39,478 HSEs within 30,604 genes. This represents 27.6% of the total genome, a similar proportion to that observed in our study.…”
Section: Discussionmentioning
confidence: 99%
“…With regard to the use of molecular markers to identify drought stress resistance in wheat and rice plants, refs. [31,[57][58][59] used quantitative trait loci (QTL) identification via marker-assisted selection to increase drought stress resistance in wheat. The authors concluded that the introgression of ancestral QTL alleles from wild wheat can increase the yield and drought resistance in domesticated wheat.…”
Section: Systematic Reviewmentioning
confidence: 99%
“…This increases the challenge of improving Agronomy 2023, 13, 2784 2 of 17 yield through phenotypic selection and hinders the progress of high-yield breeding [12]. Yield is primarily influenced by three factors: thousand kernel weight, kernel number per spike, and spike number per unit area [13][14][15][16]. It is also influenced by grain-related traits or yield components, such as ear weight and spike length [17].…”
Section: Introductionmentioning
confidence: 99%
“…Through genome-wide association studies (GWASs) utilizing thousands to millions of data points generated by low-cost genotyping platforms [23], the genetic architecture of yield and yield components has been reported in much previous research [16,[24][25][26][27][28][29][30][31][32][33][34][35][36][37]. Wheat has a planting history of over 4000 years in China and is widely cultivated in 10 major agricultural ecological regions, each with its own unique genetic characteristics [38,39].…”
Section: Introductionmentioning
confidence: 99%